"A Plague Broke Out among Them": Reflections on the Bible and the Pandemic. (July 2023) - Kaminsky, Joel S.
This essay seeks to utilize ideas and texts found in the Hebrew Bible in order to historically contextualize the COVID-19 pandemic and to illuminate various existential, religious, political, and ethical issues raised by the current pandemic and our responses to it.